Pengembangan Museum Sang Nila Utama: Riau Dalam Perspektif Cultural Studies - Rahmanto, Nadya Putri; Syafril, Syafril; Nopriyasman, Nopriyasman (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to critically examine the development of the Sang Nila Utama Museum in Riau through a Cultural Studies perspective. The primary focus of the study is to analyze the forms, factors, impacts, and meanings of the museum's development. This descriptive qualitative research employed participant observation, interviews, and documentation studies. Data analysis combined deconstruction theory to dismantle the museum's dominant narrative and cultural development theory to understand the museum's role as an agent of cultural transformation.The results indicate that the development includes updating historical narratives, repositioning collections, aesthetic improvements, and the integration of digital technology (virtual tours, interactive media, and QR codes). This development is influenced by both internal factors (limited human resources and funding) and external factors (technological advancements and low public interest). Positive impacts identified include increased visitor interest and the opening of educational spaces, while negative risks include potential commercialization and narrative imbalance. Fundamentally, this development shifts the museum's role from a passive collection space to an inclusive and critical space for discussion and the production of meaning, relevant to the Malay-Riau cultural identity.